Implementing Knowledge Management in School Environment: Teachers' Perception - Minhong Wang; Kai Wing Chu; Allan H.K. Yuen (Knowledge Management & E-Learning: An International Journal, 2011)
Knowledge Management (KM) can be used as an alternative strategy by schools to help teachers equipped with relevant skills to face the challenges to improve performance as its uses in commercial sectors. However, little research has been undertaken on how KM can be applied to school environment. To put KM into action, it is crucial to understand teachers’ perception of KM at the outset. The study was carried out in a typical Hong Kong secondary school. Interviews, based on relevant KM models, were conducted to understand teachers’ perception of KM. We found that knowledge sharing, people, culture and knowledge storage with IT support were regarded as important from the interviewees’ points of view. Most interviewees might accept that KM can help improve their practice but it needs the support of various dimensions such as people, culture, IT and management. The findings may provide insights for KM implementation in the school.